2019
DOI: 10.1177/0363546519881411
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Look at the Evaluation and Treatment of Adult Borderline and Frank Hip Dysplasia

Abstract: Background: Adult hip dysplasia is often diagnosed according to the lateral center-edge angle (LCEA). Patients with frank hip dysplasia (LCEA <20°) traditionally require treatment with bony realignment through a periacetabular osteotomy (PAO) and/or derotational femoral osteotomy, while patients with borderline hip dysplasia (BHD) present a challenging treatment dilemma, as it remains unknown when they should be treated with hip arthroscopy and/or a PAO. Purpose: To perform a narrative review to report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 60 publications
1
57
0
Order By: Relevance
“…PAO has demonstrated to effectively alter the natural history of developmental dysplasia of the hip (DDH) 56 ; however, the role of PAO in borderline dysplasia is still an open question, with limited data available. 22,39 With 39 patients with borderline dysplasia, McClincy et al 38 reported good results after PAO, with a 94% survivorship rate at minimum 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAO has demonstrated to effectively alter the natural history of developmental dysplasia of the hip (DDH) 56 ; however, the role of PAO in borderline dysplasia is still an open question, with limited data available. 22,39 With 39 patients with borderline dysplasia, McClincy et al 38 reported good results after PAO, with a 94% survivorship rate at minimum 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, Kraeutler et al 22 noted that hip arthroscopy alone as an initial surgical treatment remains a viable option in patients with borderline dysplasia. Nonetheless, the authors emphasized that these studies represented short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCEA, acetabular coverage ratio, sharp angle and Tönnis angle were measured by Digimizer software (version 5.4.6) before and after the PAO. DDH is generally believed to exist with an LCEA<20° (24,25), acetabular coverage ratio < 75%(26), sharp angle>40° (27)and Tönnis angle>10°(28). In addition, according to previous studies (24,25), the preoperative LCEA was graded as follows: LCEA<5°, 5°< LCEA<20°, and LCEA>20°.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…DDH is generally believed to exist with an LCEA<20° (24,25), acetabular coverage ratio < 75%(26), sharp angle>40° (27)and Tönnis angle>10°(28). In addition, according to previous studies (24,25), the preoperative LCEA was graded as follows: LCEA<5°, 5°< LCEA<20°, and LCEA>20°. According to Wells et al (21), a postoperative LCEA was graded as 20° < LCEA<38° and LCEA >38°.…”
Section: Outcome Measuresmentioning
confidence: 99%